2012
DOI: 10.1515/nanoph-2012-0006
|View full text |Cite
|
Sign up to set email alerts
|

Progress on one-dimensional zinc oxide nanomaterials based photonic devices

Abstract: One-dimensional nanostructures hold the most attractive and excellent physiochemical characteristics which exhibit the paramount infl uence on the fundamental and technological nanoelectronic as well as nanophotonic applications. In this review article, we present a detailed introduction to the diverse synthetic procedures which can be utilized for the fabrication of single-, planar-and three-dimensional ZnO nanostructures. More specifi cally, a thorough discussion regarding luminescence characteristics of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 160 publications
2
19
0
2
Order By: Relevance
“…[60][61][62][63] The UV peak is due to the excitonrecombination process while the visible emission centered at about $600 nm ranging from 480 to 800 nm is associated with oxygen vacancies due to the formation of deep levels in the band gap; this observation is also consistent with results reported by other groups. 7 In particular, Willander et al 61 have reported a comprehensive review on the subject.…”
Section: -50supporting
confidence: 91%
See 2 more Smart Citations
“…[60][61][62][63] The UV peak is due to the excitonrecombination process while the visible emission centered at about $600 nm ranging from 480 to 800 nm is associated with oxygen vacancies due to the formation of deep levels in the band gap; this observation is also consistent with results reported by other groups. 7 In particular, Willander et al 61 have reported a comprehensive review on the subject.…”
Section: -50supporting
confidence: 91%
“…Therefore characterization depends on the nature and structure of the imperfection and the electronic states of the solid. [59][60][61][62][63]67,68 In particular, all the defects discussed above play a key role in streamlining the physical and chemical properties of semiconductor materials directly associated with the structural and electronic order-disorder effects which can exist in ZnO nanocrystals with different charged states or in a neutral state typically represented by V [60][61][62][63]72,73 which are generated in the rapid crystallization of such materials during the MAH process, and have been reported in this study. In this case, experimental results presented in Fig.…”
Section: -66mentioning
confidence: 62%
See 1 more Smart Citation
“…The attraction to ZnO nanowires/nanostructures is due to many reasons such as the wide band gap (3.37 eV) combine with relatively large exciton binding energy (60 meV). Zinc oxide also possesses excellent chemical stability, electrical, optical, piezoelectric and pyro-electric properties [7][8][9]. Among the different methods of synthesis of ZnO NWs, the low temperature hydrothermal method is considered as a promising technique.…”
Section: Introductionmentioning
confidence: 99%
“…Since the direct bandgap semiconductor zinc-oxide (ZnO) has a large exciton binding energy (~60 meV), ZnO has been regarded as one of the most suitable candidates that can realize highly efficient exciton-lasing at room temperature [1,2]. In addition, ZnO is widely used for various functional devices such as gas sensors and photovoltaic devices [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%